From the Editor - Judith A. Holton (Grounded Theory Review: An International Journal)
This issue of the Review presents a new paper by Barney Glaser. Jargonizing: The use of the grounded theory vocabulary is the first chapter in Dr. Glaser’s new book to be published later this year by Sociology Press. Using secondary analysis with a recent cache of published papers on various versions of grounded theory, Glaser has produced a grounded theory of the use of GT vocabulary to legitimate GT’s remodelling as a qualitative method. Jargonizing most certainly helps to explain the multitude of references to GT in scholarly journals yet the seeming dearth of good classic grounded theory papers in these same journals!